Severe beta-blocker overdose in a 65-year-old female - Marzęda, Paweł; Kościuk, Andrzej; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Population of people over 65 years old is one of the groups of the greatest risk of suicide attempt. In this age range the highest suicide rate that results in death is observed. Metabolism alterations and co-morbidities development with age may play major role in increasing suicide rate. Accidental and intentional drug over-ingestions are more common for people with numerous prescriptions and comorbid conditions. Overdose in such patients can pose great threat to patients life. Aim of the study: The purpose of this study is to depict course of β-adrenolitics and benzodiazpines poisoning on the base of case report. Materials and methods: The analysis of the patient's medical history and the review of available literature in the PubMed and Google Scholar databases. Results: The 65-year-old female, was brought by emergency medical services to the Toxicology Clinic due severe drug poisoning. Upon admission patient was unconscious, intubated, on ventilator, in overall severe condition. She presented symptoms of circulatory insufficiency. History revealed overdose of β-adrenolitics and benzodiazepines. The application of proper pharmacological treatment and heart pacing resulted in gradual improvement of patients condition. After one-week stay she was discharged home in good condition. Conclusions: Course of β-adrenolitics poisoning with addition of benzodiazepines poses great threat, especially when one suffers from numerous comorbidities. Therefore, due to wider availability of drugs and rising number of suicide attempts, as well as events of medication errors, it is crucial to be aware of elder people problems and prevent such situations.